Pengaruh Current Ratio dan Total Asset Turnover serta Debt Ratio terhadap Return On Asset Pada Perusahaan Sub Sektor Perkebunan yang Terdaftar di Bursa Efek Indonesia - Luh Sumertini; Wayan Cipta (Jurnal Akuntansi Profesi, 2022)
This research aims to examine the effect of the current ratio, total asset  turnover, and debt ratio of return on assets both simultaneously and partially. The research design is quantitative causal. The subjects of this research is plantation sub-sector companies listed on the Indonesia Stock Exchange and the objects of research are the current ratio, total asset turnover, debt ratio and return on assets. The population is consisted of 17 companies in the plantation sub-sector listed on the Indonesia Stock Exchange. Data were collected by documents recording, and analyzed by multiple linear regression analysis.  The results show that: (1) current ratio, total asset turnover and debt ratio have a significant effect on return on assets, (2) current ratio has a positive and significant effect on return on assets with, (3) total asset turnover has a positive and significant effect on  return on assets, (4) debt ratio has a negative and significant effect on return on assets. Keyword: current ratio, total asset turnover, debt ratio, dan return on asset